Ocean acidification dampens physiological stress response to warming and contamination in a commercially-important fish (Argyrosomus regius) - Sampaio, Eduardo (2020)
Increases in carbon dioxide (CO2) and other greenhouse gases emissions are changing ocean temperature and carbonate chemistry (warming and acidification, respectively). Moreover, the simultaneous occurrence of highly toxic and persistent contaminants, such as methylmercury, will play a key role in further shaping the ecophysiology of marine organisms. Despite recent studies reporting mostly additive interactions between contaminant and climate change effects, the consequences of multi-stressor exposure are still largely unknown. Here we disentangled how Argyrosomus regius physiology will be affected by future stressors, by analysing organ-dependent mercury (Hg) accumulation (gills, liver and muscle) within isolated/combined warming (ΔT=4°C) and acidification (ΔpCO2=1100μatm) scenarios, as well as direct deleterious effects and phenotypic stress response over multi-stressor contexts. After 30 days of exposure, although no mortalities were observed in any treatments, Hg concentration was enhanced under warming conditions, especially in the liver. On the other hand, elevated CO2 decreased Hg accumulation and consistently elicited a dampening effect on warming and contamination-elicited oxidative stress (catalase, superoxide dismutase and glutathione-S-transferase activities) and heat shock responses. Thus, potentially unpinned on CO2-promoted protein removal and ionic equilibrium between hydrogen and reactive oxygen species, we found that co-occurring acidification decreased heavy metal accumulation and contributed to physiological homeostasis. Although this indicates that fish can be physiologically capable of withstanding future ocean conditions, additional experiments are needed to fully understand the biochemical repercussions of interactive stressors (additive, synergistic or antagonistic).